The failure of moroccan companies : A narrative review - SNOUSSI , Nawal (Revue Internationale des Sciences de Gestion, 2025)
In recent decades, the global economy has faced several major and unexpected crises, including the 2008 financial crisis, the COVID-19 pandemic in 2020, and the Russo-Ukrainian war in 2022. These events have had profound repercussions on the global economy, resulting in reduced production, rising unemployment, declining investments, and increased inflation. During these periods of economic turbulence, some businesses were unable to maintain their operations and filed for bankruptcy due to their inability to adapt quickly to changes, while others strengthened their resilience. This article aims to identify points of convergence among the factors of business failure in the Moroccan context, based on a comparative analysis of several case studies. In addition, it proposes an integrative model of the determinants of business failure, specifically adapted to the Moroccan context, in order to bridge theoretical insights with practical realities and provide a more holistic analytical framework.